1982
DOI: 10.3109/00016358209041118
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of silver soldered orthodontic wires

Abstract: The amounts of metals liberated from silver soldered stainless steel and cobalt-chromium orthodontic wires were measured. Measurements were taken after 3 days and 24 days immersion in 0.9% sodium chloride solution. High amounts of copper and zinc and some cadmium from the silver solder were found. The silver soldered stainless steel wire corroded more than the cobalt-chromium type, and liberated more nickel and chromium than did the cobalt-chromium wires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 3 publications
2
24
0
3
Order By: Relevance
“…• The workpiece must be cooled down gradually to avoid mechanical stresses and crystallization defects resulting from differing thermal expansion coefficients of wire and solder [22]. • The surfaces must be carefully polished after the soldering process, since pores, inhomogeneities and poorly trimmed surfaces encourage susceptibility to corrosion [2,5,6]. • Prior to insertion of an orthodontic appliance, the dental technician should control the quality of each solder joint according to the criteria set out above and repair or replace any displaying defective solders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• The workpiece must be cooled down gradually to avoid mechanical stresses and crystallization defects resulting from differing thermal expansion coefficients of wire and solder [22]. • The surfaces must be carefully polished after the soldering process, since pores, inhomogeneities and poorly trimmed surfaces encourage susceptibility to corrosion [2,5,6]. • Prior to insertion of an orthodontic appliance, the dental technician should control the quality of each solder joint according to the criteria set out above and repair or replace any displaying defective solders.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of a solder joint depends on its mechanical stability [12,20,31,32], the degree of contact [8], the alloying properties of the materials to be soldered [11,22,31,32], the extent of entrapments and holes in the soldering area [1,8,31,32], and corrosion resistance [2,8]. It has frequently been shown that silver solder connections of steel alloys are susceptible to corrosion due to galvanic reactions and overheating [2,6,9,25,29]. Besides undesirable functional impairment, corrosion products may give rise to biological effects [15,16,26], although the extent of clinically relevant damage to health is as yet largely unknown [10].…”
Section: Introduction and Issuementioning
confidence: 99%
“…Silver soldering has been shown to increase nickel release from stainless steel arch wires. 13 The RME appliance, because it is made of stainless steel and includes several silversoldering seams, may have leaked nickel to an extent that exceeded the individual threshold of our patient. Whether the allergic reaction would have occurred similarly to that seen with standard fixed appliances can only be speculated upon.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, even though the brackets in group B are fabricated with a more resistant alloy, they present a welded area between the body and base of the brackets, which tends to increase susceptibility to corrosion. 3,19,21,24 Comparisons with in vitro studies are necessary, yet limited, because of variations in methodology. The first variable is the immersion solution; the most often solutions used are 0.05% or 0.9% saline solution or artificial saliva with different compositions.…”
Section: Discussionmentioning
confidence: 99%